The proposal of rural taxation by Caio Prado Jr. and its contemporary use - Ortega, Any Marise (Pontifícia Universidade Católica de São Paulo, 2004)
This article recovers the context of development of the conceptions of Caio Prado Jr. About the agrarian issue: the theoretical impact of the political action of the Left in the pre 64’s. More specifically, the mechanism of the agrarian reform conceived by the author which isunderpinned on territorial taxation. Thus, it is possible the comparison of the present time when the issue has been put back again.